The Kinetics of Selective Biological Transport: V. Further Data on the Erythrocyte-Monosaccharide Transport System - Miller, D. M. (1971)
Measurements of the rate of loss of sugar from human erythrocytes into sugar-free solutions were made as a function of sugar concentrations. The half-saturation concentration of this process was found to be different from those half-saturation concentrations previously measured by other methods. These data, together with a number of similar data from former publications, are summarized in tabular form and their use in assessing postulated transport mechanisms is illustrated by consideration and rejection of a mechanism in which the transport process is assumed to be the result of a protein conformational change.